Déjà-vu from the nineties: is there a perspective for anti-endotoxin strategies to improve the outcome of multiple trauma patients? - Histing, Tina; Menger, Michael D. (Journal of Thoracic Disease, 2016)
A recent cohort study of Charbonney et al. indicates that multiple trauma patients develop endotoxemia also in the absence of Gram-negative infection. This is most probably due to an increase of gut permeability. Non-survivors as well as patients with cardiovascular dysfunction and multiple organ failure (MOF) show significantly higher endotoxin levels at 24 h after injury compared to survivors and patients without MOF. These results are like a déjà-vu from the nineties of the last century, where several studies reported endotoxemia during the initial 24 h after multiple trauma with development of MOF and death at endotoxin levels >10 and >12 pg/mL, respectively. Of interest, other multiple trauma patient studies in the nineties have shown endogenous anti-endotoxin antibody production in survivors and reduced antibody production in non-survivors, which died from MOF. Although all these studies have pointed towards a mechanistic role of endotoxin in the fatal outcome after multiple injuries, clinical anti-endotoxin studies are still lacking. Thus, the future perspective must be prospective randomized multicenter trials, which have to elucidate the capability of anti-endotoxin treatment strategies to improve outcome in multiple trauma patients.